SETH1 and SETH2, Two Components of the Glycosylphosphatidylinositol Anchor Biosynthetic Pathway, Are Required for Pollen Germination and Tube Growth in Arabidopsis - Lalanne, Eric (American Society of Plant Biologists, 2004)
Glycosylphosphatidylinositol (GPI) anchoring provides an alternative to transmembrane domains for anchoring proteins to the cell surface in eukaryotes. GPI anchors are synthesized in the endoplasmic reticulum via the sequential addition of monosaccharides, fatty acids, and phosphoethanolamines to phosphatidylinositol. Deficiencies in GPI biosynthesis lead to embryonic lethality in animals and to conditional lethality in eukaryotic microbes by blocking cell growth, cell division, or morphogenesis. We report the genetic and phenotypic analysis of insertional mutations disrupting SETH1 and SETH2, which encode Arabidopsis homologs of two conserved proteins involved in the first step of the GPI biosynthetic pathway. seth1 and seth2 mutations specifically block male transmission and pollen function. This results from reduced pollen germination and tube growth, which are associated with abnormal callose deposition. This finding suggests an essential role for GPI anchor biosynthesis in pollen tube wall deposition or metabolism. Using transcriptomic and proteomic approaches, we identified 47 genes that encode potential GPI-anchored proteins that are expressed in pollen and demonstrated that at least 11 of these proteins are associated with pollen membranes by GPI anchoring. Many of the identified candidate proteins are homologous with proteins involved in cell wall synthesis and remodeling or intercellular signaling and adhesion, and they likely play important roles in the establishment and maintenance of polarized pollen tube growth.